2002
DOI: 10.1002/ajh.10262
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and adolescent large‐cell lymphoma (LCL): A review of the children's cancer group experience

Abstract: We reviewed the clinical characteristics, treatment, and outcome of 67 children with localized and 212 with disseminated large-cell lymphoma (LCL) treated during a 20-year period in 5 consecutive Children's Cancer Group (CCG) non-Hodgkin's lymphoma (NHL) trials. Clinical outcomes for patients treated on the four earlier studies with moderatedose chemotherapy administered over 12-18 months were compared with patients treated most recently with short, intensive therapy. Median age at diagnosis was 12 years (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 35 publications
2
25
0
2
Order By: Relevance
“…In the study performed by Cairo et al (11), a LDH level above 1000 IU/L was determined to be an independent prognostic factor in lymphomas. In other studies, LDH level as a prognostic criterion in lymphoma was reported to be 500 IU/L or lower or higher than two-fold of the normal (11)(12)(13)(14). In our study, the mean LDH value was found to be 665 IU/L.…”
Section: Discussionsupporting
confidence: 53%
“…In the study performed by Cairo et al (11), a LDH level above 1000 IU/L was determined to be an independent prognostic factor in lymphomas. In other studies, LDH level as a prognostic criterion in lymphoma was reported to be 500 IU/L or lower or higher than two-fold of the normal (11)(12)(13)(14). In our study, the mean LDH value was found to be 665 IU/L.…”
Section: Discussionsupporting
confidence: 53%
“…[1][2][3][4][5][6][7][8] About 90% of histologic subtypes of childhood de novo high-risk (BM with or without CNS) B-NHL are of the aggressive subtype, including mature B-cell acute lymphoblastic leukemia (B-ALL), Burkitt lymphoma (BL) and Burkitt-like (BLL) histology and to a lesser extent, an intermediate subtype, diffuse large B-cell lymphoma (DLBCL). [9][10][11] Despite an improvement in overall survival (S) with multiagent intensive chemotherapy, there is a significant incidence of serious morbidity, including grade III/IV mucositis (40%-70%), systemic infection (60%-80%), myelosuppression (80%-100%), prolonged hospitalization (median 10-14 days during each induction cycle), and a toxic death rate of 1%-2% in remission with potential long-term cardiac and gonadal toxicities and secondary malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Currently, localized or limited stage NHL (stage I to II) has an approximate 95% to 100% 5-year event-free survival (EFS) rate. Furthermore, the prognosis for children with advanced-stage disease (stage III to IV) has doubled from a 5-year EFS of approximately 40% 30 years ago to more than 80%.…”
Section: Introductionmentioning
confidence: 99%